Discourse Markers in Audiovisual Translating - Chaume, Frederic (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractDiscourse markers are mostly used for the production of coherent conversation and, especially, to make clear the speaker’s intentions and show what the speaker intends to do with words. In general, there is no one-to-one correspondence between two languages in the field of discourse markers: most of the time their correlates in the target language have not the same pragmatic meaning, constituting a usual pitfall in translation. In the domain of audiovisual translating these particles are often omitted for the sake of brevity or for the meaningful and stroking presence of the parallel image. In this article we will examine the translation from English into Spanish of the particles now, oh, you know, (you) see, look, and I mean, which appear in the cult movie Pulp Fiction and examine how their omission in the translation affects the balance between interpersonal meaning and semantic meaning.